Association of the Receptor for Advanced Glycation End Products Gene Polymorphisms and Circulating RAGE Levels with Diabetic Retinopathy in the Chinese Population. (4th November 2013) - Yang, Li; Wu, Qunhong; Li, Yuan; Fan, Xiaohong; Hao, Yanhua; Sun, Hong; Cui, Yu; Han, Liyuan
Abstract : Objectives . This study investigated the association between polymorphisms in the receptor for advanced glycation end products (RAGE) gene and the susceptibility to diabetic retinopathy (DR) in a Chinese population and identified a correlation between serum-soluble RAGE (sRAGE) levels and DR risk. Materials and Methods . We enrolled 1040 patients with type 2 diabetes mellitus: 372 patients with DR and 668 without retinopathy (NDR). All polymorphisms were genotyped by time-of-flight mass spectrometry. Serum levels of sRAGE were assayed by enzyme-linked immunosorbent assays. The interaction of SNPs was analyzed by multifactor dimensionality reduction (MDR). Results . The frequency of the SS genotype for the G82S polymorphism was 12.4% in the DR group and 6.6% in the NDR group; this difference was significant. G82S was associated with sRAGE levels. Specifically, after adjustments for age, sex, duration, and glucose metabolism, serum sRAGE levels were significantly higher in DR subjects with the S/S genotype than in NDR subjects in general. In the DR group, subjects with the G/S genotype had lower sRAGE levels than subjects with the G/G or S/S genotype (P < 0 . 01 ). The best multilocus genetic interaction model was assessed using the MDR method; 2184A/G, 1704G/T, G82S, and −429T/C were identified. Conclusions . The findings suggest that the G82S polymorphism in the RAGE gene is associated with DR risk, and G82S was associated with circulating levels of sRAGE. The mechanism by which G82S polymorphism modulates the sRAGE levels remains to be elucidated.